Assessing Australian Monetary Policy in the Twenty-First Century - Isaac Gross; Andrew Leigh (Institute of Labor Economics (IZA), 2022)
Using the Reserve Bank of Australia's MARTIN model we compare actual monetary policy decisions to a counterfactual in which the cash rate is set according to an optimal simple rule. We find that monetary policy played a crucial role in avoiding a potential recession in 2001 and mitigating the downturn in 2008-2009. By contrast we find that the cash rate was too high during 2016-2019, keeping inflation below the Reserve Bank's target band. Optimal monetary policy in 2016-2019 would have involved a substantially lower cash rate and would have produced significantly better employment outcomes.
Keywords: E47; E52; E58; 330; optimal monetary policy; unemployment; output gap; inflation